Hyperalgesic and edematogenic effects of peptides isolated from the venoms of honeybee (Apis mellifera) and neotropical social wasps (Polybia paulista and Protonectarina sylveirae) - Brigatte, P. [UNESP]; Cury, Y.; de Souza, B. M. [UNESP]; Baptista-Saidemberg, Nicoli B. [UNESP]; Saidemberg, D. M. [UNESP]; Gutierrez, V. P.; Palma, Mario Sergio [UNESP] (Springer, 2011)
Stings by bees and wasps, including Brazilian species, are a severe public health problem. The local reactions observed after the envenoming includes typical inflammatory response and pain. Several studies have been performed to identify the substances, including peptides that are responsible for such phenomena. The aim of the present study is to characterize the possible nociceptive (hyperalgesic) and edematogenic effects of some peptides isolated from the venoms of the honeybee (Apis mellifera) and the social wasps Polybia paulista and Protonectarina sylveirae, in addition to characterize some of the mechanisms involved in these phenomena. For this purpose, different doses of the peptides mellitin (Apis mellifera), Polybia-MP-I, N-2-Polybia-MP-I (Polybia paulista), Protonectarina-MP-NH2 and Protonectarina-MP-OH (Protonectarina sylveirae) were injected into the hind paw of mice. Hyperalgesia and edema were determined after peptide application, by using an electronic von Frey apparatus and a paquimeter. Carrageenin and saline were used as controls. Results showed that melittin, Polybia-MP-I, N-2-Polybia-MP-I, Protonectarina-MP-NH(2) and Protonectarina-MP-OH peptides produced a dose- and time-related hyperalgesic and edematogenic responses. Both phenomena are detected 2 h after melittin, Polybia-MP-I, N-2-Polybia-MP-I injection; their effects lasted until 8 h. In order to evaluate the role of prostanoids and the involvement of lipidic mediators in hyperalgesia induced by the peptides, indomethacin and zileuton were used. Results showed that zileuton blocked peptide-induced hyperalgesia and induced a decrease of the edematogenic response. on the other hand, indomethacin did not interfere with these phenomena. These results indicate that melittin, Polybia-MP-I, N-2-Polybia-MP-I, Protonectarina-MP-NH(2), and Protonectarina-MP-OH peptides could contribute to inflammation and pain induced by insect venoms.
Keywords: Hyperalgesia; Inflammation; Apis mellifera; Polybia paulista; Protonectarina sylveirae; Peptides